Development of Android-Based Interactive Learning Media Assisted by Smart Apps Creator to Improve Science Learning Outcomes in Elementary Schools - Siti Muvidah Nur Afifah; Novi Setyasto (Postgraduate, University of Mataram, 2025)
This research is motivated by the minimal use of technology as a learning medium which has an impact on low student learning outcomes. The purpose of this study is to develop an interactive learning media design based on Android with the help of Smart Apps Creator and to test the aspects of feasibility, practicality, and effectiveness. The research method used is Research and Development (R&D) with the Borg and Gall model. The data collection process is carried out through test techniques (posttest and pretest) and non-test (documentation, questionnaires, interviews, and observations). The results of the product validation assessment by expert validators showed a percentage score of 93.57% and 92%, with a very feasible category. The results of filling out the response questionnaire showed that the interactive learning media designed by the researcher received a very positive response from students and teachers. The results of the pretest and posttest showed that the learning media designed by the researcher was able to improve student learning outcomes, as shown by an increase in the average pretest score of 54.17 to 84.57 at the time of the posttest and the N-gain test value reached 0.71 with high criteria. Therefore, interactive learning media based on Android using Smart Apps Creator has proven to be feasible and practical to be used in the learning process and is effective in improving student learning outcomes in the content of science subjects in grade IV.